Desain E-Commerce Rumah Hijab Boutique Berbasis Android - RD Kusumanto; Mohammad Fadhli (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2019)
Muslim hijab clothes in today's era are increasingly in demand, especially Indonesian women, it is evident that more and more commercial and online figures sell Muslim hijab clothing which continues to grow every day because the interest of buyers also increases, but because many businessmen are interested in opening hijab Muslimah business in business increasingly stringent, it takes an innovation in product marketing in order to compete. E-Coommerce design which is currently very popular is one of the strategies in marketing products by businessmen, E-Commerce utilizes technological developments such as websites and androids connected to the internet network. The use of technology like this can reach a wide range of marketing but with not so much capital, and extensive marketing can provide benefits for businessmen because they can increase sales turnover. The use of the website is very much applied by business people, but the use of websites and android can optimize product marketing, because android is an efficient mobile device that can be carried anywhere, so sales and purchases can be done anywhere.